2020
DOI: 10.3390/polym12071442
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Polymer Coated Au Nanoparticles Prepared via RAFT-Assisted Encapsulating Emulsion Polymerization and Click Chemistry

Abstract: The use of reversible addition-fragmentation chain transfer (RAFT)-assisted encapsulating emulsion polymerization (REEP) has been explored to prepare diverse types of colloidal stable core–shell nanostructures. A major field of application of such nanoparticles is in emergent nanomedicines, which require effective biofunctionalization strategies, in which their response to bioanalytes needs to be firstly assessed. Herein, functional core–shell nanostructures were prepared via REEP and click chemistry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In this section, we start with an introduction of the discovery of plasmon‐driven photochemistry from SERS technique and then focus on the recent advances in the plasmon‐mediated activation and reaction of small nonpolar molecules such as H 2 , O 2 , N 2 , CO 2 , and CH 4 . Plasmon‐driven processes like polymerization reactions, [ 43–45 ] photochemical and photo‐electrochemical (PEC) water splitting, [ 46–49 ] and degradation of dye molecules [ 50,51 ] are not involved.…”
Section: Plasmon‐driven Photocatalytic Reactionsmentioning
confidence: 99%
“…In this section, we start with an introduction of the discovery of plasmon‐driven photochemistry from SERS technique and then focus on the recent advances in the plasmon‐mediated activation and reaction of small nonpolar molecules such as H 2 , O 2 , N 2 , CO 2 , and CH 4 . Plasmon‐driven processes like polymerization reactions, [ 43–45 ] photochemical and photo‐electrochemical (PEC) water splitting, [ 46–49 ] and degradation of dye molecules [ 50,51 ] are not involved.…”
Section: Plasmon‐driven Photocatalytic Reactionsmentioning
confidence: 99%
“…Polymers made by RAFT polymerization are ideal candidates for GNP functionalization as the RAFT endfunctionality can be directly used for modifications. Initially, the RAFT endgroup was hydrolyzed to liberate the thiol group for functionalization, but later on it was shown that the RAFT functionality itself is sufficient to stabilize GNP …”
Section: Introductionmentioning
confidence: 99%
“…Polymers prepared by RAFT have been used in many different fields, notably in preparation of biomaterials (implants, scaffolds, coatings, drug, gene delivery, etc. ), [ 226–230 ] sensing and detection, [ 231,232 ] coatings and patterning, [ 233–235 ] electronics, [236] nanocomposite, [ 235,237–240 ] and vitrimers. [ 241 ] One of the most recent and emerging applications of polymers and nanoparticles prepared by RAFT is membranes for separation.…”
Section: Novel Applications Of Raftmentioning
confidence: 99%